Biological nitrification inhibition (BNI) in Brachiaria pastures: a novel strategy to improve eco-efficiency of crop-livestock systems and to mitigate climate change - Moreta, Danilo; Arango, Jacobo; Sotelo Cabrera, Mauricio Efren; Vergara, Daniel; Rincón, Álvaro; Ishitani, Manabu; Castro, Aracely; Miles, John W.; Peters, Michael; Tohme, Joseph M.; Subbaraoa, Guntur V.; Rao, Idupulapati M. (International Center for Tropical Agriculture, 2014)
Up to 70% of the nitrogen (N) fertilizers applied to agricultural systems is lost due to nitrification and denitrification. Nitrification is a microbiological process that generates nitrate (NO3-) and promotes the loss of N fertilizers by leaching and denitrification. Nitrification and denitrification are the only known biological pro-cesses that generate nitrous oxide (N2O), a powerful greenhouse gas contributing to global warming. There is an urgent need to suppress nitrification processes in soil to improve N recovery and N use efficiency (NUE) of agricultural systems and to mitigate climate change (Subbarao et al.2012). Certain Brachiariagrasses (B. humidicola) can suppress soil nitrification by releas-ing biological nitrification inhibitors (BNIs) from roots, thereby reducing N2O emissions. This phenomenon, termed biological nitrification inhibition (BNI), has been the subject of recent research to characterize and validate the concept under field conditions (Subbarao et al.2009). Advances on 3 aspects of BNI research are reported here: (1) gene quantification of soil nitrifying microor-ganisms to determine BNI activity in B. humidicola; (2) screening of B. humidicolabreeding materials to identify hybrids with contrasting levels of BNI; and (3) quantifi-cation of the BNI residual effect from B. humidicolaon N recovery and agronomic NUE of a subsequent maize crop.